Alternative method for determining API degrees of petroleum in contaminated soil by FTIR - F.J. Guzmán-Osorio; R.H. Adams; V.I. Domínguez-Rodríguez; C.E. Lobato-García; A. Guerrero-Peña; J.R. Barajas-Hernández; E. Baltierra-Trejo (Egyptian Journal of Petroleum)
A method was developed to determine °API from the relative abundance of polar and aliphatic functional groups as measured by FTIR. Twenty-two samples of petroleum were collected from the southern region of Mexico and analyzed by FTIR using an Attenuated Total Reflectance (ATR) accessory. API gravity was run in parallel using the convention hydrometer method (ASTM D6822-12b). Variables were analyzed for principal components and a minimum of squares regression. API gravity of the petroleum used was between −8.8 and 41.5. For correlation, an index of the relative abundance of polar functional groups vs. saturates was developed. Data from calibration gave an R2 = 0.9632 and a standard error of 0.0129, with an absolute error of 0.0104. During the validation (with petroleum from contaminated sites), the results gave an R2 = 0.9024, with a standard error estimated at 0.0307 and an absolute mean error of 0.0199. Thus, the determination of API degrees of petroleum extracted from contaminated soil was shown to be viable using FTIR-ATR. The algorithm was developed to fit well for the whole range of crudes, from extra heavy (<10 °API) to super light (>39 °API) crudes. This method is simple, quick, does not require extensive sample preparation, uses very small sample proportions (<1 g) and produces only a minimum of waste as compared to the conventional (hydrometer) method. Keywords: Functional groups, Specific gravity, API degrees, Infrared, Petroleum